2018
DOI: 10.31290/jpk.v7i1.293
|View full text |Cite
|
Sign up to set email alerts
|

Keterampilan Menginterpretasikan Hasil Penimbangan Pada KMS Terkait Pengetahuan, Pelatihan Dan Keaktifan Kader Di Kota Bogor

Abstract: Kartu Menuju Sehat (KMS) adalah kartu yang memuat kurva pertumbuhan normal anakberdasarkan indeks antopometri berat badan menurut umur. Tujuan penelitian ini adalah untukmengetahui hubungan antara pengetahuan, pelatihan dan keaktifan kader dengan keterampilan dalammenginterpretasikan hasil penimbangan pada KMS balita di wilayah kerja Puskesmas Bogor Barat,kota Bogor. Penelitian ini merupakan penelitian analitik dengan rancangan penelitian cross-sectional.Sampel yang digunakan adalah kader posyandu di 5 (lima) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
2
1
0
1
Order By: Relevance
“…The skills of the cadres in filling in the KMS showed that most of the community health workers were already skilled in filling in the KMS (61.5%), but there were also quite a lot of unskilled cadres, namely 15 people (38.5%). This is in line with several studies which show relatively the same thing, that not all cadres are skilled in completing KMS(19) (20).…”
Section: Skills Of Cadres In Completing Kmssupporting
confidence: 92%
See 1 more Smart Citation
“…The skills of the cadres in filling in the KMS showed that most of the community health workers were already skilled in filling in the KMS (61.5%), but there were also quite a lot of unskilled cadres, namely 15 people (38.5%). This is in line with several studies which show relatively the same thing, that not all cadres are skilled in completing KMS(19) (20).…”
Section: Skills Of Cadres In Completing Kmssupporting
confidence: 92%
“…The results of this study indicate that there is a significant relationship between working status and skills in completing the KMS. This is in line with research by Afifah (2021) that there is a relationship between employment status and skills in completing KMS (20). Unemployed cadres tend to be more skilled in completing the KMS.…”
Section: Skills Of Cadres In Completing Kmssupporting
confidence: 91%
“…In this age group between 20 and 40 the level of maturity and memory of the cadres are at a better stage [7]. Yahya (2006) the older the person does not correlate with the better their knowledge [8] The education level of 45.9% of the respondents is high school graduates Stages or levels of education are stages of continuous education, which are determined based on the level of development of students, the level of complexity of the learning materials and the method of presentation of the materials [9]. The high level of education will generally be accompanied by an increase in one's understanding.…”
Section: Resultsmentioning
confidence: 99%
“…Berdasarkan hasil pengamatan atau observasi pada 15 kader di salah satu posyandu di Kecamatan Bogor Barat, 10 kader di antaranya hanya mampu menimbang dan mengisi pada buku penimbangan. Untuk mengisi pada grafik berat badan, membaca, dan menginterpretasikan hasil, kader tersebut masih belum mampu (Suhartika & Ekayanthi, 2016). Didasari oleh hal tersebut, peneliti akan berfokus pada evaluasi pelaksanaan pengumpulan data antropometri panjang dan tinggi anak di posyandu Kota Bogor.…”
Section: Pendahuluanunclassified